Rezension von: Hackenberg, Michael, Books in Artisan Homes of Sixteenth-Century Germany - Wunder, Gerd (Württembergisch Franken, 1987)
Michael Hackenberg: Books in Artisan Homes of Sixteenth-Century Germany. In: Journal of Library History 21, 1986, S. 72-91.